Heparin modulates intracellular cyclic AMP in human trabecular bone cells and adherent rheumatoid synovial cells. Issue 4 (August 1984) - Crisp, A J; Roelke, M S; Goldring, S R; Krane, S M
Abstract : Cells were cultured from explants of human trabecular bone excised from eight patients and incubated usually for 20 minutes with bovine parathyroid hormone, salmon calcitonin, prostaglandin E2, or heparin. The intracellular content of cyclic AMP was measured by radioimmunoassay and was significantly increased by parathyroid hormone in four, by calcitonin in two, by prostaglandin E2 in eight, and by heparin in seven out of eight cultures. In the two cultures containing calcitonin-responsive cells heparin inhibited the cyclic AMP response induced by calcitonin. Heparin did not affect the cyclic AMP response to parathyroid hormone or prostaglandin E2. Heparin also increased the cyclic AMP content of cultured adherent rheumatoid synovial cells. It is proposed that, in certain situations of focal pathological bone resorption, although concentrations of circulating hormones may be normal, the local release of products such as heparin may modify the effect of hormones which regulate connective tissue homoeostasis. local changes in hormone responses could contribute to the enhanced bone resorption associated with inflammatory processes such as rheumatoid arthritis.